Structure Characteristics of the Krestovozdvizhenskaya Production-Related Placer - Plyusnina, K. I.; Goldyrev, V. V.; Bryukhov, V. N. (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2025)
The article discusses the structure of the Krestovozdvizhenskaya technogenic placer deposit on the western slope of the Middle Urals, located in a former diamond mining quarry. The main characteristic features of placer structure are highlighted. It is proposed to use the results of assessment of the placer deposit as a prototype for small gold deposits to evaluate the resources of similar gold occurrences in the comparable geological conditions.